Exploring the Impact of Digital Transformation and Banking Factors on the Financial Performance of Conventional Banks Listed on the Indonesian Stock Exchange - Mela Aryasari; Bahtiar Usman (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This research aims to examine the impact of Internet and Security, Capital Adequacy Ratio, Non-Performing Loans, Operating Expenses to Operating Income, Loan to Deposit Ratio, Bank Size, Loans, Exchange Rate, and Gross Domestic Product on the performance of conventional banks from 2017 to 2022. The sample consists of conventional banks listed on the Indonesia Stock Exchange during this period. Data is sourced from a time series covering the years from 2017 to 2022 for independent variables and bank performance as the dependent variable. The methodology employed is Ordinary Least Squares, utilizing Eviews 10 software for logistic regression analysis. The results indicate that Internet and Security, Capital Adequacy Ratio, Loan to Deposit Ratio, Bank Size, and Gross Domestic Product significantly affect changes in the performance of conventional banks, as measured by Return on Assets (ROA). Specifically, Internet Security, Bank Size, Exchange Rate, and Gross Domestic Product show a positive impact, while Capital Adequacy Ratio, Operating Expenses, Non-Performing Loans, and Loans exhibit a negative effect. Finance managers can leverage this research to gain insights into the key factors contributing to the performance of conventional banks in Indonesia, particularly as influenced by digital financial services and advancements in technology and information, which significantly impact the banking sector. By understanding these factors, managers can make more informed decisions to effectively manage their banks and enhance performance. Additionally, the findings provide valuable information to investors regarding the primary determinants of conventional bank performance in Indonesia, enabling them to take appropriate actions for investment and achieve high returns on their investments.